Alloy and ceramic composite coating and preparation method thereof

By constructing an alloy and ceramic composite coating on the surface of the diamond tool, the problems of interface cracking and wear caused by differences in thermal expansion coefficients and high-temperature chemical instability during the cutting process are solved, and the tool's high hardness, wear resistance and oxidation resistance are improved.

CN120719362APending Publication Date: 2025-09-30TSINGHUA SHENZHEN INTERNATIONAL GRADUATE SCHOOL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510959928.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-10
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

When cutting high-hardness materials, diamond tools are prone to interface cracking, coating peeling and wear due to differences in thermal expansion coefficients and high-temperature chemical instability, which affects their service life.

Method used

An alloy and ceramic composite coating is constructed on the surface of the diamond tool. Chromium, tungsten-nickel, and molybdenum-nickel alloy coatings are deposited in sequence by electroplating, combined with silicon carbide and alumina ceramic powders to form a dense protective layer to improve thermal stability and wear resistance.

Benefits of technology

It significantly improves the hardness, wear resistance and oxidation resistance of the tool, prolongs its service life and reduces the damage to the tool caused by thermal stress and chemical reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120719362A_ABST
    Figure CN120719362A_ABST
Patent Text Reader

Abstract

The invention discloses an alloy and ceramic composite coating and a preparation method thereof. The preparation method comprises the following steps: adding raw materials including chromium sulfate, sodium tungstate, sodium molybdate, nickel sulfate, sodium sulfate, sodium citrate, boric acid and ceramic powder into a solvent to prepare an electroplating solution; after the surface of a base material is subjected to mechanical polishing, alkali washing oil removal, acid pickling activation and nickel pre-plating, the base material serves as a cathode and an anode electrode to be put into electroplating liquid together, a direct-current power source is adopted for electroplating, the electroplating voltage is selected to range from 10 V to 12 V, the current density is selected to range from 12 A / dm to 20 A / dm, electroplating deposition is conducted for 30 min to 70 min, and the alloy and ceramic composite coating is obtained. According to the preparation method disclosed by the invention, various metal alloys are electroplated on the surface of the diamond cutter by adjusting the electroplating potentials according to different electroplating potentials of different metals, so that the hardness, wear resistance and high-temperature stability of the diamond cutter are remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of precision machining, and in particular to an alloy and ceramic composite coating and a preparation method thereof. Background Art

[0002] In recent years, the rapid development of industries such as aerospace, automotive, and electronics has driven the widespread application of difficult-to-cut materials such as carbon fiber composites (CFRP), high-silicon aluminum alloys, ceramics, and cemented carbide. At the same time, modern manufacturing demands continuously increase workpiece surface stability, dimensional accuracy, and machining efficiency. Against this backdrop, traditional carbide tools are no longer able to meet the machining demands of these high-hardness, high-wear-resistant materials. Diamond tools, such as polycrystalline diamond (PCD) and chemical vapor deposition (CVD) diamond tools, due to their exceptional hardness and wear resistance, are an ideal choice for precision machining of these high-hardness, high-wear-resistant materials.

[0003] However, diamond tools still face multiple technical bottlenecks in practical applications: due to the -6 / K) and commonly used substrate materials (such as WC-Co, about 5×10 -6 The significant difference in thermal expansion coefficients (K) between diamond and steel leads to thermal stress accumulation during high-temperature sintering or cutting, resulting in interfacial cracking or coating delamination. Chemical instability at high temperatures further exacerbates the problem. Diamond undergoes oxidation reactions when heated in oxygen-containing environments to produce gaseous oxides. When cutting iron-based materials, localized high temperatures can also induce a phase transition from diamond to graphite, causing it to lose its superhard properties. Tool substrates primarily made of alloys like copper and iron have relatively low hardness, making them susceptible to edge wear under continuous cutting or impact, thus limiting the tool's overall service life.

[0004] To overcome these limitations, it is imperative to construct a protective layer on the surface of diamond cutting tools through surface modification technology. This protective layer must possess both high-temperature protection and wear resistance, effectively blocking thermal oxidation and phase change reactions during machining while also improving the tool's wear resistance, increasing tool hardness, and strengthening cutting edge support. Summary of the Invention

[0005] The technical problem to be solved by the present application is to overcome the defects of the above-mentioned technology and provide an alloy and ceramic composite coating and a preparation method thereof. By electroplating, a layer of alloy and ceramic composite coating is constructed on the surface of the substrate to improve the thermal stability and wear resistance of the substrate.

[0006] This application primarily studies the effects of process parameters and coating composition on the coating. Using a solution containing primary salts (chromium sulfate, nickel sulfate, sodium tungstate, sodium molybdate), a ligand, a buffer, a conductive agent, and ceramic powders of silicon carbide and alumina, the electroplating solution was used. By controlling the plating potential according to the different metals, a chromium layer doped with ceramic powder, a tungsten-nickel layer doped with ceramic powder, and a molybdenum-nickel layer doped with ceramic powder were sequentially deposited on the substrate surface. The resulting alloy and ceramic composite coating comprised of different metals and ceramic powders was obtained. The density of the coating was optimized by optimizing the plating solution's acidity and alkalinity. The chromium layer, acting as a base layer directly bonded to the substrate, possesses high hardness and can share frictional stress, reducing direct wear on the substrate and thus extending its life. The tungsten-nickel alloy layer, layered atop the chromium layer, takes advantage of tungsten's ultra-high melting point (3422°C) to inhibit softening and maintain structural stability in high-temperature cutting environments. The tungsten-nickel coating serves as the outermost layer, while the molybdenum-nickel coating significantly reduces frictional heat thanks to molybdenum's extremely low coefficient of friction (0.1 to 0.2). The cemented carbide in this alloy-ceramic composite coating effectively improves the matrix's hardness and wear resistance. It also isolates certain substrates, such as diamond tools, from oxygen to a certain extent, helping to prevent oxidation of the diamond tool during the high temperatures generated during the cutting process, which can reduce its hardness. Furthermore, the addition of silicon carbide and alumina ceramic powders reduces the transfer of external heat inward while also partially dissipating tool wear during the cutting process, thereby enhancing the tool's wear resistance. By constructing a layer of alloy-ceramic composite coating on the substrate surface, the substrate's hardness, thermal stability, and wear resistance are simultaneously enhanced, extending its service life.

[0007] The above-mentioned method for preparing an alloy and ceramic composite coating comprises the following steps: Step (1) preparing an electroplating solution: adding a certain proportion of raw materials to a solvent and then stirring to mix them evenly to form a solution, wherein the raw materials include chromium sulfate, sodium tungstate, sodium molybdate, nickel sulfate, sodium sulfate, sodium citrate and boric acid, and then adding ceramic powder mixed with a dispersant to the solution to obtain an electroplating solution; Step (2) pre-plating treatment: mechanically polishing, alkaline washing and degreasing, acid washing and activation, and pre-nickel plating are performed on the surface of the substrate; Step (3) electroplating process: the substrate is used as a cathode electrode and immersed in an electroplating solution together with an anode electrode for electroplating, and a chromium plating layer doped with ceramic powder, a tungsten-nickel alloy plating layer doped with ceramic powder, and a molybdenum-nickel alloy plating layer doped with ceramic powder are deposited in sequence by electroplating to obtain an alloy and ceramic composite coating; Step (4) post-plating treatment: after the electroplating is completed, the substrate is taken out, rinsed and dried to obtain the substrate with the alloy and ceramic composite coating on the surface, and then passivation and hydrogen removal treatment are performed.

[0008] In some embodiments, the electroplating process in step (3) is as follows: first, the pH of the electroplating solution is controlled to be between 2.0 and 3.0 by adding sulfuric acid, the current density is adjusted to 10A / dm² to 15A / dm², the voltage is adjusted to 10V, and the temperature is adjusted to 35°C to 40°C for the first electroplating, and the electroplating time of the first electroplating is 50 minutes to 70 minutes, and a hard chromium plating layer doped with ceramic powder is electroplated on the surface of the substrate; then, the pH of the electroplating solution is adjusted to 7.0 to 9.0, the current density is adjusted to 10A / dm² to 15A / dm², the voltage is adjusted to 12V, and the temperature is adjusted to 60 ℃ to 80℃ for secondary electroplating, the electroplating time of the secondary electroplating is controlled at 30 minutes to 50 minutes, and a tungsten-nickel alloy plating layer doped with ceramic powder is electroplated on the surface of the hard chromium plating layer doped with ceramic powder; then, the pH of the electroplating solution is adjusted to 8.0 to 10.0 by adding ammonia water, the current density is set to 15A / dm² to 20A / dm², the voltage is set to 12V, and the temperature is adjusted to 60℃ to 80℃ for three electroplating, the electroplating time of the three electroplating is controlled at 30 minutes to 40 minutes, and a molybdenum-nickel alloy plating layer doped with ceramic powder is electroplated on the surface of the tungsten-nickel alloy plating layer doped with ceramic powder to obtain an alloy and ceramic composite plating layer.

[0009] In some embodiments, in step (1), in the electroplating solution, the concentration of chromium sulfate is 50 g / L to 100 g / L, the concentration of sodium tungstate is 50 g / L to 100 g / L, the concentration of sodium molybdate is 50 g / L to 100 g / L, the concentration of nickel sulfate is 100 g / L to 200 g / L, the concentration of sodium sulfate is 150 g / L to 250 g / L, the concentration of sodium citrate is 300 g / L to 400 g / L, and the concentration of boric acid is 30 g / L to 60 g / L.

[0010] In some embodiments, in step (1), the ceramic powder includes silicon carbide with a particle size of 0.5 μm to 1.5 μm and aluminum oxide with a particle size of 0.5 μm to 1.5 μm, and the dispersant is a 10 wt % polyethylene glycol aqueous solution.

[0011] In some embodiments, the silicon carbide powder, the aluminum oxide powder, and the polyethylene glycol aqueous solution are mixed in a ratio of 1g:1g:100ml, and the concentration of the silicon carbide powder in the electroplating solution is 20g / L to 50g / L, and the concentration of the aluminum oxide powder is 10g / L to 30g / L.

[0012] In some embodiments, in step (2), the substrate is a diamond tool; in step (3), the anode electrode is graphite or DSA.

[0013] In some embodiments, in step (2), the mechanical polishing is performed using sandpaper with a mesh size of 200 to 800.

[0014] In some embodiments, in step (2), the alkaline washing and degreasing process is: placing the substrate after the mechanical polishing into an alkaline degreasing solution comprising NaOH, Na2CO3, Na3PO4 and a surfactant, and ultrasonicating for 5 to 10 minutes; in the alkaline degreasing solution, the concentration of NaOH is 30 g / L to 50 g / L, the concentration of Na2CO3 is 20 g / L to 30 g / L, the concentration of Na3PO4 is 20 g / L to 30 g / L, and the concentration of the surfactant is 5 mL / L to 10 mL / L.

[0015] In some embodiments, in step (2), the pickling activation process is: placing the substrate after the alkaline washing and degreasing into a mixed pickling solution including H2SO4 and H2O2, and soaking it at room temperature for 30 seconds, wherein the mass percentage of H2SO4 in the mixed pickling solution is 10%, and the mass percentage of H2O2 is 3%.

[0016] In some embodiments, in step (2), the pre-nickel plating process is as follows: placing the activated cutting tool into a plating solution comprising NiSO4·6H2O (250 g / L to 350 g / L), NiCl2·6H2O (50 g / L to 100 g / L) and H3BO3 (40 g / L to 80 g / L), adjusting the pH of the pre-plating solution to 4.0 to 5.0, adjusting the current density to 3 A / dm², and performing pre-nickel plating for 3 to 7 minutes; the concentration of the NiSO4·6H2O in the pre-plating solution is 250 g / L to 350 g / L, the concentration of the NiCl2·6H2O is 50 g / L to 100 g / L, and the concentration of the H3BO3 is 40 g / L to 80 g / L.

[0017] The beneficial effects of this application are: This application utilizes a direct current electroplating method to deposit an alloy and ceramic composite coating on the surface of a substrate (such as a diamond tool). This preparation method utilizes a solution containing multiple metal salts as the electrolyte. By controlling the electroplating potential, a metal coating composed of different metals can be produced on the substrate surface. As a base layer directly bonded to the substrate, the chromium coating possesses high hardness, sharing frictional stress and reducing direct wear on the diamond, thereby extending tool life. Its dense structure isolates corrosive media, preventing rust or oxidation of the substrate. Furthermore, by blocking direct contact between the diamond and the workpiece, it effectively inhibits chemical diffusion reactions at high temperatures. The tungsten-nickel alloy coating layer atop the chromium coating, due to tungsten's ultra-high melting point (3422°C), inhibits coating softening in high-temperature cutting environments, maintaining structural stability. The molybdenum-nickel coating, as the outermost layer, significantly reduces cutting friction heat and the risk of tool sticking due to molybdenum's extremely low coefficient of friction (0.1 to 0.2). The sequential electrodeposition of chromium, tungsten, and molybdenum coatings achieves a comprehensive performance optimization of "high strength, strong bonding, and high-temperature resistance." The reason for this is that all three metal coatings possess high strength and rigidity. Chromium, with its strong adhesion to the diamond substrate, effectively prevents subsequent coating flaking as a base layer. Tungsten, with its extremely high melting point (3422°C), ensures the coating remains intact during high-temperature cutting. Its high hardness (HV 3000-4000) creates a gradient hardness profile with the chromium coating, effectively dissipating stress. The outermost molybdenum layer forms a dense MoO3 oxide film at high temperatures, protecting the inner layer from oxidation. The alloy coating in the composite coating prepared in this application effectively improves the hardness and wear resistance of the substrate matrix and reduces high-temperature oxidation reactions in some substrates, such as diamond tools. The physical barrier effect of the composite coating reduces the contact between diamond and oxygen, preventing oxidation during high-speed cutting, which could destabilize the diamond tool structure. Furthermore, the hard metals, such as chromium, in the composite coating prevent chemical reactions between elements like iron and cobalt and diamond at high temperatures, extending the life of the diamond tool. On the other hand, the ceramic powders contained in the alloy and ceramic composite coating, such as aluminum oxide and silicon carbide, have excellent thermal insulation properties, effectively reducing the transfer of external heat to the substrate. Furthermore, due to the excellent wear resistance of the ceramic powders, they can also share some of the wear on the substrate, thereby improving the substrate's wear resistance. Therefore, by constructing a layer of alloy and ceramic composite coating on the substrate surface, the substrate's hardness, wear resistance, and structural stability can be significantly improved, and the oxidation resistance of substrates such as diamond cutting tools can also be enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 These are the X-ray diffraction test results of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 in this application.

[0019] Figure 2 These are SEM images of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present application.

[0020] Figure 3 These are the Rockwell hardness test results of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present application.

[0021] Figure 4 These are the friction and wear test results of Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3 of the present application.

[0022] Figure 5 These are the Rockwell hardness test results of Examples 2, 3, and 4 of the present application.

[0023] Figure 6 These are the friction and wear test results of Examples 2, 3, and 4 of the present application. DETAILED DESCRIPTION

[0024] The embodiments of the present application will be described in detail below with reference to the examples, but it will be understood by those skilled in the art that the following examples are merely illustrative of the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, the conditions are carried out according to conventional conditions or manufacturer recommendations. The reagents or instruments used are not specified by the manufacturer and are conventional products that can be purchased commercially. The present application provides a preparation method for constructing an alloy and ceramic composite coating on a diamond surface. The preparation method comprises the following steps: Step (1) preparing an electroplating solution: adding a certain proportion of raw materials to a solvent and then stirring to mix them evenly to form a solution, wherein the raw materials include chromium sulfate, sodium tungstate, sodium molybdate, nickel sulfate, sodium sulfate, sodium citrate and boric acid, and then adding ceramic powder mixed with a dispersant to the solution to obtain an electroplating solution.

[0025] Step (2) Pre-plating treatment: The substrate surface is subjected to mechanical polishing, alkaline washing for degreasing, pickling for activation and pre-nickel plating.

[0026] Step (3) electroplating process: the substrate is used as a cathode electrode and immersed in an electroplating solution together with an anode electrode, and a chromium plating layer doped with ceramic powder, a tungsten-nickel alloy plating layer doped with ceramic powder, and a molybdenum-nickel alloy plating layer doped with ceramic powder are deposited in sequence by electroplating to obtain an alloy and ceramic composite coating; Step (4) post-plating treatment: after the electroplating is completed, the substrate is taken out, rinsed and dried to obtain the substrate having the alloy and ceramic composite coating on the surface, and then the substrate is passivated and dehydrogenated.

[0027] In step (1) of this embodiment, the specific steps of preparing the electroplating solution are as follows: adding 50g / L to 100g / L of chromium sulfate, 50g / L to 100g / L of sodium tungstate, 50g / L to 100g / L of sodium molybdate, 100g / L to 200g / L of nickel sulfate, 300 to 400g / L of sodium citrate, 30 to 60g / L of boric acid, 150g / L to 250g / L of sodium sulfate, hydroxyacetic acid, a stabilizer consisting of sodium sulfite, neutral amino acid and PAMAM in a mass ratio of 1:1.5:0.2 to deionized water, and mechanically stirring to mix to form a uniform solution; then using hydrochloric acid added with 5wt% HF and 20wt% HNO3 to pickle the silicon carbide powder with a particle size of 0.5μm to 1.5μm, and using 20wt% NaHCO3 solution to pickle the silicon carbide powder with a particle size of 0.5μm to 1.5μm. The aluminum oxide powder with a diameter of 1 to 1.5 μm was alkali washed, and then the silicon carbide powder, aluminum oxide powder and 10 wt% polyethylene glycol aqueous solution were mixed and stirred at a ratio of 1 g:1 g:100 ml and ultrasonically treated to obtain a uniformly dispersed mixture, which was added to the above solution, and then mechanically stirred for 1 hour and allowed to stand for 12 hours to obtain an electroplating solution.

[0028] The chromium plating layer in the preparation method uses a trivalent chromium plating solution containing chromium sulfate, the tungsten-nickel alloy plating solution uses nickel sulfate and sodium tungstate as primary salts, and the molybdenum-nickel alloy plating solution uses nickel sulfate and sodium molybdate as primary salts. These primary salts provide the metal ions required for electroplating, and the four primary salts are chemically stable and do not interfere with each other. Sodium citrate is used as a complexing agent, boric acid and glycolic acid as buffers, and sodium sulfate as a conductive agent. Stabilizers include sodium sulfite, a neutral amino acid, and PAMAM in a mass ratio of 1:1.5:0.2.

[0029] The concentration of chromium sulfate in the electroplating solution can be 50g / L to 100g / L, the concentration of sodium tungstate in the electroplating solution can be 50g / L to 100g / L, the concentration of sodium molybdate in the electroplating solution can be 50g / L to 100g / L, and the concentration of nickel sulfate in the electroplating solution can be 100g / L to 200g / L. The diffusion rate of each metal ion within the above concentration range in the electroplating solution is moderate, which can form a uniform and dense coating and reduce pinholes and nodules in the metal coating.

[0030] The sodium citrate acts as a ligand to form a complex with the metal ions, preventing hydrolysis and precipitation of the metal ions. A suitable concentration of 300 to 400 g / L of sodium citrate in the electroplating solution is sufficient. This concentration range allows the sodium citrate to completely complex the metal ions in the solution, ensuring a stable ion formation and improving the uniformity of the coating.

[0031] The boric acid is used as a buffer in the electroplating solution to maintain the stability of the pH value of the electroplating solution. During the electroplating process, the substrate as the cathode will release hydrogen gas, OH - The accumulation leads to an increase in the pH value of the plating solution. Boric acid, as a stable weak acid, can react with OH - The boric acid content in the plating solution is preferably between 30 and 60 g / L. This concentration range provides sufficient buffering capacity to maintain a stable pH in the plating solution.

[0032] The sodium sulfate, as a conductive agent in the electroplating solution, can increase the conductivity of the electroplating solution. Sodium sulfate is chemically stable and does not react with other components in the electroplating solution. A suitable sodium sulfate content in the electroplating solution can be 150 g / L to 250 g / L. Maintaining the sodium sulfate content within this range can improve the conductivity of the electroplating solution.

[0033] The glycolic acid and boric acid synergistically maintain the acid-base stability of the electroplating solution, preventing drastic pH fluctuations. It is milder than inorganic acids (such as sulfuric acid), reducing the risk of substrate corrosion. Furthermore, compared to other organic acids (such as oxalic acid), glycolic acid is more biodegradable, reducing wastewater treatment pressure. The optimal glycolic acid content in the electroplating solution is 15g / L to 30g / L. This concentration range provides sufficient buffering capacity to maintain a stable pH in the plating solution.

[0034] The stabilizer consists of sodium sulfite, neutral amino acids, and PAMAM in a mass ratio of 1:1.5:0.2. Sodium sulfite has an antioxidant effect and is compatible with multiple ligands (such as EDTA and glycolic acid), without affecting the pH of the plating solution. Neutral amino acids can form stable complexes with metal ions, inhibiting hydrolysis or oxidation, making them an environmentally friendly and non-toxic alternative to traditional cyanide ligands. PAMAM can encapsulate metal ions to form size-controlled nanoclusters, preventing metal ion aggregation and ensuring uniform deposition during the electroplating process. The optimal stabilizer content in the plating solution is 30 g / L to 40 g / L. Adding the stabilizer within this concentration range ensures a reducing environment in the plating solution, preventing excessive complexation, and maintaining viscosity.

[0035] The particle size of the silicon carbide powder is 0.5 μm to 1.5 μm, and the particle size of the aluminum oxide powder is 0.5 μm to 1.5 μm. Experiments show that silicon carbide powder and aluminum oxide powder in this particle size range are evenly dispersed in the plating solution and can be evenly deposited to form a protective layer. The appropriate concentration of silicon carbide powder in the plating solution is 20 g / L to 50 g / L, and the appropriate concentration of aluminum oxide powder is 10 g / L to 30 g / L. The coating formed in the above concentration range has the best wear resistance. If the content of ceramic powder in the plating solution is too low, the wear resistance of the coating will be poor. If the content of ceramic powder in the plating solution is too high, the distribution of the coating may be uneven, hindering the normal deposition of metal ions.

[0036] The acid washing of the silicon carbide powder can remove the oxide layer on the surface of the silicon carbide powder and activate the surface of the silicon carbide powder, so that the silicon carbide surface is positively charged and more easily absorbs metal ions, thereby promoting the co-deposition of the silicon carbide powder.

[0037] The alkali washing of the aluminum oxide powder can remove the oxide layer on the surface of the aluminum oxide powder, increase the hydrophilicity of the aluminum oxide powder, and enable the aluminum oxide powder to be evenly dispersed in the plating solution.

[0038] The silicon carbide powder, aluminum oxide powder, and a 10 wt% polyethylene glycol aqueous solution were mixed uniformly at a ratio of 1 g:1 g:100 ml and then added to the electroplating solution. The 10 wt% polyethylene glycol aqueous solution was prepared using polyethylene glycol with a molecular weight of 4000. The silicon carbide powder and aluminum oxide powder mutually attract the metal ions, and the silicon carbide powder and aluminum oxide powder are deposited on the substrate surface simultaneously with the deposition of the metal ions.

[0039] The electroplating solution is allowed to stand for 12 hours to eliminate bubbles in the electroplating solution, stabilize the dispersion of the raw material components, and evenly suspend the ceramic powder particles. The electroplating solution obtained is ultimately homogenized and chemically stable.

[0040] In step (2) of this embodiment, the specific steps of pre-plating treatment are as follows: first, use 200-800 mesh sandpaper to polish the surface of the substrate step by step, and diamond polishing paste can be used if a mirror surface is required; the polished substrate is placed in an alkaline degreasing solution including NaOH, Na2CO3, Na3PO4, and a surfactant and ultrasonically degreased for 5 minutes to 10 minutes; in the alkaline degreasing solution, the concentration of NaOH is 30g / L to 50g / L, the concentration of Na2CO3 is 20g / L to 30g / L, the concentration of Na3PO4 is 20g / L to 30g / L, and the concentration of the surfactant is 5mL / L to 10mL / L; then the degreased substrate is placed in a mixed pickling solution including H2SO4 and H2O2, and immersed at room temperature for 30 seconds for activation, wherein the mass percentage of H2SO4 in the mixed pickling solution is 10%, and the mass percentage of H2O2 is 3%. Afterwards, the activated substrate is placed in a pre-plating solution consisting of NiSO4·6H2O (250g / L), NiCl2·6H2O (50g / L) and H3BO3 (40g / L). The pH of the pre-plating solution is adjusted to 4.0 to 5.0, the current density is adjusted to 3A / dm², and pre-nickel plating is performed for 3 to 7 minutes to obtain a substrate that has completed pre-treatment.

[0041] Mechanical grinding of the substrate can remove the oxide layer, rust and burrs on the surface of the substrate, which is conducive to the uniform deposition of the coating and avoids "skipping" or poor bonding of the coating.

[0042] By performing alkaline washing and degreasing treatment on the mechanically polished substrate, grease, dirt and some oxides on the surface of the substrate can be removed to ensure a strong bond between the coating and the substrate.

[0043] The surfactant used in the alkali cleaning and degreasing can be selected from one or more of sodium lauryl sulfate, sodium dodecylbenzene sulfonate, fatty alcohol polyoxyethylene ether, and alkylphenol polyoxyethylene ether. The substrate after alkali cleaning and degreasing is subjected to an acid cleaning and activation treatment to remove the oxide film, passivation layer, and trace organic matter on the surface of the substrate, thereby further ensuring a strong bond between the coating and the substrate.

[0044] By pre-nickel plating the substrate, the bonding between the coating and the substrate can be improved, corrosion of the substrate can be prevented, and the quality of subsequent coatings can be improved.

[0045] In step (3) of this embodiment, the specific steps of electroplating are as follows: using the substrate as the cathode and the graphite as the anode, immersing the substrate and the anode electrode in the prepared electroplating solution, and starting electroplating, firstly, by adding sulfuric acid, the pH of the electroplating solution is controlled to be between 2.0 and 3.0, the current density is adjusted to 10A / dm² to 15A / dm², the voltage is adjusted to 10V, and the temperature is adjusted to 35°C to 40°C for a first electroplating, the electroplating time of the first electroplating is controlled to be 50 minutes to 70 minutes, and a hard chromium coating is electroplated on the surface of the substrate. Then, by adding ammonia water, the pH of the electroplating solution is adjusted to 7.0 to 9.0, the current density is adjusted to 10A / dm² to 15A / dm², the voltage is adjusted to 12V, and the temperature is adjusted to 60°C to 80°C for a second electroplating, the electroplating time of the second electroplating is controlled to be 30 minutes to 50 minutes, and a tungsten-nickel alloy coating of doped ceramic powder is electroplated on the surface of the hard chromium coating of doped ceramic powder. Then, the pH of the electroplating solution is adjusted to 8.0 to 10.0 by adding ammonia water, the current density is adjusted to 15A / dm² to 20A / dm², the voltage is adjusted to 12V, and the temperature is adjusted to 60°C to 80°C for three electroplatings. The plating time of the three electroplatings is controlled at 30 minutes to 40 minutes. The molybdenum-nickel alloy coating doped with ceramic powder is electroplated on the surface of the tungsten-nickel alloy coating doped with ceramic powder to obtain an alloy and ceramic composite coating.

[0046] In step (4) of this embodiment, the specific steps of post-plating treatment are as follows: after the electroplating is completed, the substrate is promptly rinsed with deionized water to avoid corrosion; then it is immersed in a 50g / L Na2Cr2O7 solution at 50°C for 30 seconds for passivation treatment; finally, it is placed in a 150°C oven for drying for 12 hours for dehydrogenation treatment.

[0047] Through passivation treatment, a dense oxide film (passivation film) can be formed on the surface of the electroplating layer. This oxide film (passivation film) can effectively block the contact of corrosive media (such as water, oxygen, chloride ions, etc.) with the coating, thereby significantly improving the corrosion resistance of the coating.

[0048] The dehydrogenation treatment diffuses hydrogen atoms from the metal by heating, thereby reducing hydrogen embrittlement, significantly improving the tensile strength and toughness of the substrate, and avoiding fracture caused by hydrogen embrittlement during use.

[0049] The technical principles of this application are as follows: By applying a DC power supply, the metal ions in the electrolyte are reduced on the surface of the cathode electrode (substrate), forming a dense, uniform coating. By adjusting the plating potential, various metal alloys can be electroplated on the substrate surface, depending on the specific metal. Silicon carbide and alumina ceramic powders are added to the plating solution to form an alloy-ceramic composite coating on the substrate surface. pH is controlled during the electroplating process to optimize the surface density of the composite coating. Ultimately, this electroplating process results in a dense alloy-ceramic composite coating. For certain substrates, such as diamond cutting tools, hard metals such as chromium and tungsten in the composite coating can effectively enhance the hardness of diamond cutting tools. Furthermore, since diamond (C) readily reacts with transition metals such as iron (Fe) and cobalt (Co) at high temperatures to form carbides (e.g., Fe3C, Co3C), or oxidizes upon exposure to oxygen at high temperatures, losing its hardness, the alloy in the composite coating prepared in this application is less likely to react with diamond and can block chemical reactions between transition metal elements such as iron and cobalt, or oxygen, and diamond at high temperatures. The ceramic protective layer composed of silicon carbide and aluminum oxide in the alloy-ceramic composite coating not only enhances the wear resistance of diamond cutting tools but also forms a thermal insulation layer, reducing the transmission of high temperatures generated locally during the cutting process to the interior of the tool, thereby maintaining the interfacial bond between the diamond and the matrix material. This also prevents the high temperatures during the cutting process from converting diamond into graphite, which reduces tool hardness. The electroplating method of the present application electroplates different metal and ceramic powders onto the surface of the substrate separately by adjusting the electroplating potential to obtain an alloy and ceramic composite coating. Hydrogen removal and passivation treatment are then performed in the later stage to avoid hydrogen embrittlement while improving the corrosion resistance of the protective layer, ultimately achieving an effective improvement in the hardness, wear resistance, and high-temperature stability of the substrate.

[0050] The technical solution of the present application will be further described below with reference to specific embodiments, but the embodiments of the invention are not limited thereto.

[0051] 1. Specific examples of the method for preparing the alloy and ceramic composite coating of the present application are as follows: Example 1 Step (1) preparing an electroplating solution: adding chromium sulfate (70 g / L), sodium sulfate (150 g / L), sodium tungstate (70 g / L), sodium molybdate (70 g / L), nickel sulfate (150 g / L), sodium citrate (350 g / L), and boric acid (40 g / L) to deionized water in proportion, and mechanically stirring to mix them evenly; then acid-washing the silicon carbide powder with a particle size of 1 μm, and alkali-washing the aluminum oxide powder with a particle size of 1 μm, and then mixing the silicon carbide powder, aluminum oxide powder, and polyethylene glycol together and ultrasonically treating them to disperse them evenly, and adding them to the electroplating solution, the silicon carbide powder concentration is (30 g / L), and the aluminum oxide powder concentration is (20 g / L), mechanically stirring for 1 hour, and standing for 12 hours to obtain the final electroplating solution.

[0052] Step (2) Pre-plating treatment: polish the surface of the diamond tool step by step with 200 mesh, 300 mesh, 500 mesh and 800 mesh sandpaper. Diamond polishing paste can be used if mirror surface is required; put the polished tool into an alkaline degreasing solution composed of NaOH (30 g / L), Na2CO3 (20 g / L), Na3PO4 (20 g / L) and surfactant (5 mL / L), and ultrasonicate for 5 to 10 minutes; then put the degreasing tool into a mixed pickling solution including H2SO4 and H2O2, and soak it at room temperature for 30 seconds for activation, wherein the mass percentage of H2SO4 in the mixed pickling solution is 10% and the mass percentage of H2O2 is 3%. Afterwards, the activated tool was placed in a plating solution consisting of NiSO4·6H2O (250g / L), NiCl2·6H2O (50g / L) and H3BO3 (40g / L), the pH was adjusted to 4.5, the current density was adjusted to 3A / dm², and pre-nickel plating was performed for 5 minutes.

[0053] Step (3) electroplating process: The diamond tool is used as the cathode and the graphite is used as the anode. The electrodes are placed in the electroplating solution for electroplating. First, the pH of the electroplating solution is adjusted to 2.0 with sulfuric acid, the current density is 12A / dm², the voltage is 10V, the temperature is 40°C, and a hard chromium coating is electroplated for 60 minutes; then, the pH is adjusted to 9.0 with ammonia water, the current density is 15A / dm², the voltage is 12V, the temperature is 60°C, and a tungsten-nickel alloy coating is electroplated for 60 minutes; then, the pH is adjusted to 10.0 with ammonia water, the current density is 20A / dm², the voltage is 12V, the temperature is 60°C, and a molybdenum-nickel alloy coating is electroplated for 30 minutes, finally obtaining an alloy and ceramic composite coating.

[0054] Step (4) Post-plating treatment: After the electroplating is completed, rinse with deionized water to avoid corrosion; then immerse it in a 50g / L Na2Cr2O7 solution at 50°C for 30 seconds for passivation treatment; finally, put it into a 150°C oven for drying for 12 hours to remove hydrogen.

[0055] Example 2 The difference from Example 1 is that the electroplating conditions of the electroplated chromium coating are different: The pH of the plating solution was adjusted to 2.0 with sulfuric acid, the current density was 6A / dm², the voltage was 10V, the temperature was 30°C, and the hard chromium coating was electroplated for 35 minutes.

[0056] Example 3 The difference from Example 1 is that the electroplating conditions of the tungsten-nickel alloy are different: The pH was adjusted to 7.0 with ammonia water, the current density was 7A / dm², the voltage was 12V, the temperature was 50°C, and the tungsten-nickel alloy coating was electroplated for 25 minutes.

[0057] Example 4 The difference from Example 1 is that the electroplating conditions of the molybdenum-nickel alloy are different: The pH was adjusted to 8.0 with ammonia water, the current density was set to 8 A / dm², the voltage was 12 V, the temperature was 50°C, and the molybdenum-nickel alloy coating was electroplated for 20 minutes.

[0058] Comparative Example 1 The difference between the preparation method of the alloy and ceramic composite coating of the diamond tool in this comparative example and the preparation method of the alloy and ceramic composite coating of the diamond tool in Example 1 is that in the preparation of the alloy and ceramic composite coating in Comparative Example 2, the pH of the plating solution during the electroplating process is acidic.

[0059] Comparative Example 2 The difference between the preparation method of the alloy and ceramic composite coating of the diamond tool in this comparative example and the preparation method of the alloy and ceramic composite coating of the diamond tool in Example 1 is that in the preparation method of the alloy and ceramic composite coating of Comparative Example 3, the electroplated metal is nickel and molybdenum, which is different from Example 1.

[0060] Comparative Example 3 The difference between this comparative example and Example 1 is that the comparative example 3 is a blank diamond tool that has not been electroplated.

[0061] The Rockwell hardness test method used in the specific implementation of this application is: 3 to 5 points were selected at the head, middle and tail of the diamond tool surface, and the surface hardness was measured using a Rockwell hardness tester (560RSSZ).

[0062] The friction and wear test method used in the specific embodiment of this application is: A constant-speed friction tester (UMT-3 testing machine) was used to perform friction and wear tests on the friction plate of Example 1 in accordance with GB / T5764-2021.

[0063] Figure 1 The X-ray diffraction test results for diamond cutting tools with alloy and ceramic composite coatings prepared in Example 1, Comparative Examples 1 and 2, and the diamond cutting tool of Comparative Example 3 are shown. The X-ray diffraction peaks of Example 1 show, in addition to the obvious diamond (C) characteristic peaks, characteristic peaks of elements such as copper, iron, chromium, and tungsten, demonstrating that the preparation method of this application successfully prepared an alloy and ceramic composite coating of chromium, tungsten, nickel-silicon carbide, and aluminum oxide on the surface of the diamond cutting tool.

[0064] Figure 2 Scanning electron microscopy (SEM) examination results of diamond tools with alloy and ceramic composite coatings prepared in Example 1, Comparative Examples 1 and 2, and the diamond tool of Comparative Example 3 show that the composite coating prepared in Example 1 has significantly better density and flatness than those in the comparative examples. This indicates that coatings obtained by electroplating chromium under acidic conditions, tungsten-nickel coatings under alkaline conditions, and molybdenum-nickel coatings under alkaline conditions have better density and flatness than those obtained by electroplating under acidic conditions throughout the process.

[0065] Figure 3 The Rockwell hardness test results of the diamond tools with alloy and ceramic composite coatings prepared in Example 1, Comparative Example 1 and Comparative Example 2, and the diamond tool of Comparative Example 3 are shown. Comparing the results of Example 1 with those of Comparative Example 3, it can be seen that the Rockwell hardness of Example 1 is significantly improved compared with that of Comparative Example 3, indicating that constructing a layer of alloy and ceramic composite coating on the surface of the diamond tool can effectively improve the hardness of the tool.

[0066] Figure 4 The results of the friction and wear tests of the diamond tools with alloy and ceramic composite coatings prepared in Example 1, Comparative Example 1 and Comparative Example 2, and the diamond tool of Comparative Example 3 are shown. The friction curve of Example 1 shows a higher friction coefficient and a more stable friction curve with smaller fluctuations, showing the highest wear resistance, indicating that the alloy and ceramic composite coating of the diamond tool prepared by the present application has excellent wear resistance. Figure 5 The Rockwell hardness test results of Example 2, Example 3 and Example 4 of this application are shown in FIG. The Rockwell hardness of Example 4 is the highest among the three, but still lower than Figure 3 In Example 1, for the chromium coating, as the current density increases, the grain size of the chromium plating decreases and the hardness of the chromium plating increases.

[0067] For tungsten-nickel coatings and molybdenum-nickel coatings, since the reduction of tungsten belongs to induced co-deposition, the increase in current density will significantly increase the tungsten / molybdenum content in the coating.

[0068] The Rockwell hardness of Example 1 is the highest among Examples 1-4, which may be because the electroplating time of Example 1 is the longest and the obtained coating is the thickest.

[0069] Figure 6 This is a graph showing the friction and wear test results of Examples 2, 3 and 4 of the present application. The friction curve of Example 2 fluctuates less and is relatively smoother than that of Examples 3 and 4, and exhibits a higher friction coefficient COF. However, the friction coefficient COF of Example 2 is still lower than that of Example 1, indicating that within a certain range, the greater the current density and the longer the electroplating time, the better the wear resistance of the obtained alloy and ceramic composite coating.

[0070] The above description is only a preferred embodiment of the present application and does not limit the patent scope of the present application. All changes, modifications, substitutions, combinations, and simplifications made using the contents of the present application specification under the inventive concept of the present application should be equivalent replacement methods, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present application.

Claims

1. An alloy and ceramic composite coating and a preparation method thereof, characterized in that: The following steps are included: Step (1) preparing an electroplating solution: adding a certain proportion of raw materials to a solvent and then stirring to mix them evenly to form a solution, wherein the raw materials include chromium sulfate, sodium tungstate, sodium molybdate, nickel sulfate, sodium sulfate, sodium citrate, and boric acid, and then adding ceramic powder mixed with a dispersant to the solution to obtain an electroplating solution; Step (2) pre-plating treatment: mechanically polishing, alkaline washing and degreasing, acid washing and activation, and pre-nickel plating are performed on the surface of the substrate; Step (3) electroplating process: the substrate is used as a cathode electrode and immersed in an electroplating solution together with an anode electrode for electroplating, and a chromium plating layer doped with ceramic powder, a tungsten-nickel alloy plating layer doped with ceramic powder, and a molybdenum-nickel alloy plating layer doped with ceramic powder are deposited in sequence by electroplating to obtain an alloy and ceramic composite coating; Step (4) post-plating treatment: after the electroplating is completed, the substrate is taken out, rinsed and dried to obtain the substrate with the alloy and ceramic composite coating on the surface, and then passivation and hydrogen removal treatment are performed.

2. The alloy and ceramic composite coating and preparation method thereof according to claim 1, characterized in that: In step (3), the electroplating process is as follows: first, by adding sulfuric acid, the pH of the electroplating solution is controlled to be between 2.0 and 3.0, the current density is adjusted to 10A / dm² to 15A / dm², the voltage is adjusted to 10V, and the temperature is adjusted to 35°C to 40°C for one electroplating, and the electroplating time of the one electroplating is 50 minutes to 70 minutes, and a hard chromium plating layer doped with ceramic powder is electroplated on the surface of the substrate; then, by adding ammonia water, the pH of the electroplating solution is adjusted to 7.0 to 9.0, the current density is adjusted to 10A / dm² to 15A / dm², the voltage is adjusted to 12V, and the temperature is adjusted to 60°C to 80°C for one electroplating. The invention relates to a method for preparing a tungsten-nickel alloy coating doped with ceramic powder by electroplating a second electroplating process, wherein the electroplating time of the second electroplating process is controlled to be 30 minutes to 50 minutes, and a tungsten-nickel alloy coating doped with ceramic powder is electroplated on the surface of the hard chromium coating doped with ceramic powder; and then the pH of the electroplating solution is adjusted to 8.0 to 10.0, the current density is adjusted to 15A / dm² to 20A / dm², the voltage is adjusted to 12V, and the temperature is adjusted to 60°C to 80°C by adding ammonia water, and the electroplating is carried out three times, wherein the electroplating time of the three electroplating processes is controlled to be 30 minutes to 40 minutes, and a molybdenum-nickel alloy coating doped with ceramic powder is electroplated on the surface of the tungsten-nickel alloy coating doped with ceramic powder to obtain an alloy and ceramic composite coating.

3. The alloy and ceramic composite coating and preparation method thereof according to claim 1, characterized in that: In step (1), in the electroplating solution, the concentration of chromium sulfate is 50 g / L to 100 g / L, the concentration of sodium tungstate is 50 g / L to 100 g / L, the concentration of sodium molybdate is 50 g / L to 100 g / L, the concentration of nickel sulfate is 100 g / L to 200 g / L, the concentration of sodium sulfate is 150 g / L to 250 g / L, the concentration of sodium citrate is 300 g / L to 400 g / L, and the concentration of boric acid is 30 g / L to 60 g / L.

4. The alloy and ceramic composite coating and preparation method thereof according to claim 1, characterized in that: In step (1), the ceramic powder includes silicon carbide with a particle size of 0.5 μm to 1.5 μm and aluminum oxide with a particle size of 0.5 μm to 1.5 μm, and the dispersant is a 10 wt % polyethylene glycol aqueous solution.

5. The alloy and ceramic composite coating and preparation method thereof according to claim 4, characterized in that: In step (1), the silicon carbide powder, the aluminum oxide powder and the polyethylene glycol aqueous solution are mixed in a ratio of 1g:1g:100ml, and the concentration of the silicon carbide powder in the electroplating solution is 20g / L to 50g / L, and the concentration of the aluminum oxide powder is 10g / L to 30g / L.

6. The alloy and ceramic composite coating and preparation method thereof according to claim 4, characterized in that: In step (2), the substrate is a diamond tool; in step (3), the anode electrode is graphite or DSA.

7. The alloy and ceramic composite coating and preparation method thereof according to claim 1, characterized in that: In step (2), the mechanical polishing is performed using sandpaper with a mesh size of 200 to 800.

8. The alloy and ceramic composite coating and preparation method thereof according to claim 1, characterized in that: In step (2), the alkaline cleaning and degreasing is as follows: placing the substrate after the mechanical polishing into an alkaline degreasing solution comprising NaOH, Na2CO3, Na3PO4 and a surfactant and ultrasonically treating for 5 to 10 minutes; in the alkaline degreasing solution, the concentration of NaOH is 30 g / L to 50 g / L, the concentration of Na2CO3 is 20 g / L to 30 g / L, the concentration of Na3PO4 is 20 g / L to 30 g / L, and the concentration of the surfactant is 5 mL / L to 10 mL / L.

9. The alloy and ceramic composite coating and preparation method thereof according to claim 1, characterized in that: In step (2), the pickling activation is as follows: placing the substrate after the alkaline washing and degreasing into a mixed pickling solution comprising H2SO4 and H2O2, and soaking it at room temperature for 30 seconds, wherein the mass percentage of H2SO4 in the mixed pickling solution is 10%, and the mass percentage of H2O2 is 3%.

10. The alloy and ceramic composite coating and preparation method thereof according to claim 1, characterized in that: In step (2), the pre-nickel plating is as follows: placing the substrate after the pickling activation into a pre-plating solution comprising NiSO4·6H2O, NiCl2·6H2O and H3BO3, adjusting the pH of the pre-plating solution to 4.0 to 5.0, adjusting the current density to 3A / dm², and performing pre-nickel plating for 3 to 7 minutes; in the pre-plating solution, the concentration of NiSO4·6H2O is 250g / L to 350g / L, the concentration of NiCl2·6H2O is 50g / L to 100g / L, and the concentration of H3BO3 is 40g / L to 80g / L.